2017
DOI: 10.1371/journal.pone.0185833
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic measurement of the quadriceps angle in dogs

Abstract: The direction of the force of the quadriceps muscle group is expressed by the value of the quadriceps angle, between the long axis of the muscle rectus femoris and the patellar ligament. This value is often modified in dogs with patellar luxation, a common orthopaedic disease of the stifle joint in both small and large dogs. The aims of the present study were to give a reference value for the quadriceps angle in healthy small and medium-large breed dogs. The medical records of healthy dogs and their pelvic lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…According to the purposes of the study, articles were classified into two main groups. The first group was the articles that focused on reporting standard methods for measurements of femoral and tibial alignments and reporting reference values [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Eleven articles from a total of 29 articles were included in this group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the purposes of the study, articles were classified into two main groups. The first group was the articles that focused on reporting standard methods for measurements of femoral and tibial alignments and reporting reference values [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Eleven articles from a total of 29 articles were included in this group.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies were performed on medium-to-large-breed dogs [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 27 , 28 , 29 , 37 , 39 , 40 ]. Eight studies evaluated small-breed dogs [ 24 , 30 , 35 , 36 , 38 , 42 , 43 , 44 ], and 14 studies evaluated a combination of small and large breeds [ 25 , 26 , 31 , 32 , 33 , 34 , 41 ]. The number of dogs included in the studies is demonstrated in Figure 2 , categorized according to the dog breeds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coxa vara of the femur and decreased FAA are typically associated with MPL (Pinna & Romagnoli, 2017). There are two proposed theories for this relationship.…”
Section: Discussionmentioning
confidence: 99%